Examining the Portrayal of U.S. Host Families and Exchange Students in Study Abroad Websites: A Content Analysis - Fanari, Alice (Journal of International Students, 2024)
This study uses a content analysis to document the representation of the homestay experience focusing on the portrayal of U.S. host families and exchange students in 16 study abroad programs’ websites. Despite the increase of international students coming to the United States for secondary education and the pressing need to recruit host families, not much is known about how study abroad websites represent the U.S. homestay experience. Results suggest that study abroad websites provide a traditional representation of U.S. host families, characterized by two White host parents (with or without children) hosting predominantly White and Asian exchange students. Inter-reality comparisons also reveal an over-representation of White host families and Black exchange students in study abroad websites, though the representation of White and Asian exchange students appeared consistent with the shares of White and Asian exchange students expected in reality. Implications for study abroad programs are discussed.